2015
DOI: 10.4236/ojn.2015.51004
|View full text |Cite
|
Sign up to set email alerts
|

Rural High School Students’ Sexual Behavior and Self-Esteem

Abstract: Background: Negative consequences for sexual health may be caused by risky sexual behavior related to attitudes, norms and self-efficacy regarding sexuality. Research has not resulted in a consensus on the associations between self-esteem and adolescents' sexual behavior. Aims and Objectives: The aim of the study was to describe high school students' sexual behavior and self-esteem, along with investigating the relationship of attitudes, norms, self-efficacy, and self-esteem to sexual risk behavior. Another ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(28 reference statements)
1
7
1
1
Order By: Relevance
“…At the individual level, no relationship was found between self-esteem and risky sexual behaviors, which is consistent with some of the literature (Rivers et al, 2013). As pointed out at the outset, findings regarding self-esteem and risky sexual behavior are conflicting, with positive, negative and null associations reported (Ganczak et al, 2017;Unis et al, 2015). A possible explanation for null findings may be the use of global as opposed to facet-specific self-esteem.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At the individual level, no relationship was found between self-esteem and risky sexual behaviors, which is consistent with some of the literature (Rivers et al, 2013). As pointed out at the outset, findings regarding self-esteem and risky sexual behavior are conflicting, with positive, negative and null associations reported (Ganczak et al, 2017;Unis et al, 2015). A possible explanation for null findings may be the use of global as opposed to facet-specific self-esteem.…”
Section: Discussionsupporting
confidence: 86%
“…Selfesteem refers to confidence in one's own worth or abilities. Results regarding the relationship between the level of self-esteem and the probability of engaging in high-risk sexual behaviors are conflicting, with authors reporting associations that are negative (Ganczak, Czubińska, Korzeń, & Szych, 2017), positive (Unis, Johansson, & Sällström, 2015) and null (Rivers et al, 2013). Risktaking can be defined as engaging in behaviors that are high in subjective desirability or excitement but that carry the potential for injury or loss (Geier, Terwilliger, Teslovich, Velanova, & Luna, 2010).…”
Section: Journal Of Social Behavioral and Health Sciencesmentioning
confidence: 99%
“…Although self-esteem and self-efficacy are good inner resources to possess, they do not always prevent risky behavior. This was seen in a study (Unis, Johansson, & S€ allstr€ om, 2015), which showed that adolescents' use of condoms was low despite good self-efficacy in condom use. Critical thinking and practical skills are ways to empower adolescents to make informed decisions regarding their sexuality (Macintyre et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…The level of item retention was set at >0.8 to establish the content validity index. Thus, any item not meeting the specified requirement was dropped for further required modifications [ 38 – 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires were then pretested among 240 adolescents to determine a Cronbach’s Alpha for their internal consistency reliability. Exploratory factor analysis was first performed for data reduction to get high weighed items above the suggested statistical thresholds (>0.3) as recommended by authors from previous studies [ 38 – 40 ].…”
Section: Methodsmentioning
confidence: 99%